Distance Estimation by Blindfolded Sighted Participants Using Echolocation. (December 2019) - Maezawa, Tomoki; Kawahara, Jun I
Auditory perceived distance can be distorted in one's internal representation. Thus, the present study examined whether blindfolded sighted participants could reduce the bias and preserve estimated distance for 5 to 15 s using echolocation. The participants performed a delayed reproduction task that consisted of testing sessions on 2 separate days in which the target distance was manipulated from 20 to 50 cm. Participants were blindfolded and asked to reproduce the distance of a target after a temporal delay of several seconds using click bursts produced by a loudspeaker. The testing session was preceded by a practice session that included training and feedback. The relationship between estimated and actual distances was approximated based on a power function and the over- and underestimation of the target distance on each test day. Although participants showed systematic bias in distance estimation on both days, participants changed their bias in the second session by shifting reproduced locations closer to their bodies. The accuracy and consistency of their responses improved across the 2 days. Neither accuracy nor consistency was affected by the retention intervals. These enhancements of performance might be due to improved hearing ability or calibration of internal spatial references through a practice session.